(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Talakua M, Suadi, Djumanto, Setyobudi E. 2022. Record of Hemiramphus lutkei Valenciennes, 1847 from Seram Sea, Maluku, Indonesia with its molecular characterization. Biodiversitas 23: 1560-1566. Hemiramphus sp. is a fish species widely distributed throughout the world. However, the area distribution of each species differs between regions. Hemiramphus archipelagicus could be found in Seram Sea, Maluku and Ekas Bay, Lombok, Hemiramphus sp. from North Maluku Sea, and H. brasiliensis from the North Minahasa Sulawesi. The identification of Hemiramphus in Indonesia uses mainly the morphological approach. This study aims to determine the morphometric and meristic character and identify the halfbeak collected from the Seram Sea, Maluku, using a molecular approach. A total of 214 fish samples were used to determine the morphometric and meristic characters of halfbeak, following the measurement method that has been developed previously. All samples of halfbeak showed similar morphological characteristics. Identification by direct sequencing of the cytochrome c oxidase subunit I (COI) gene was conducted from selected samples. The halfbeak caught in the Seram Sea had an elongated flat body shape, the dorsal part of the body is blue-green, the tip of the lower beak is sharp, enlarged towards the base in the oral cavity; the lower beak is reddish-orange and longer than the upper beak. The fin formula of halfbeak from the Seram Sea is D.13-15, P.9-12, V.5-6, A.9-12, C.7/8, and the number of scales at the lateral line is 52-58. Based on molecular identification, the halfbeak species from the Seram Sea was confirmed as Hemiramphus lutkei with a genetic distance of 0.0055 compared to H. lutkei from India, and a genetic distance of 0.0540 with H. balao.